Etude de l’activité antimicrobienne des huiles essentielles d’Artemisia herba alba de la région d’El Kantara (wilaya de Biskra) et de Mentha pulegium de la foret de Mesra (wilaya de Mostaganem) - Bechiri, Souhila; Tahar Mezedek, Salima (My University, 2018)
This work was realized in order to evaluate the antimicrobial activity of the essential oils of Artemisia herba alba and Mentha pulegium from the regions of Biskra and Mostaganem. These last were extracted by steam distillation of water, the total yields obtained from dry leaves of Artemisia herba alba and fresh leaves of Mentha pulegium are respectively 0.28% and 0.23%. The antibiogram showed that Doxycycline (DXT30) had the most remarkable inhibitory effect with an maximal inhibition zone of 27 mm for the reference strain Pseudomonas aeruginosa ATCC 27853. No remarkable inhibitory activity by Calvulanic Acid against Escherichia coli strains ATCC 25922, Bacillus cereus ATCC 10876, P. aeruginosa ATCC 27853, and Proteus mirabilis ATCC 35659. Regarding to the antifungigram, Econazole and Clotrimazol caused an inhibition of the two fungal strains tested; it is noted that Econazole has an extreme effect with a 22 mm inhibition for Aspergillus brasiliensis ATCC 16404. The evaluation of the antimicrobial activity by the aromatogram method showed that the essential oil of Artemisia herba alba has a great inhibitory action on the growth of the five germs tested, namely, Escherichia coli, Bacillus cereus , P. aeruginosa, Proteus mirabilis, and Candida albicans, with zones of inhibition ranging between 19 and 33mm. While the essential oils of Mentha pulegium have been effective on Escherichia coli, Bacillus cereus, Proteus mirabilis, Aspergillus brasiliensis, and Candida albicans which is the most sensitive with a 26mm inhibition zone. We concluded the work by the method of direct contact method (MIC) which confirmed the results obtained by the aromatogram for the two essential oils. This confirms the effectiveness of these essential oils.
Keywords: Artemisia herba alba; Mentha pulegium; huiles essentielles; activité antimicrobiennes.; الزیوت الأساسیة; الشیح; الفلیو; النشاط المضاد للمیكروبات; essential oils; antimicrobial activity.